Pitting corrosion resistance with shielded metal arc welding and post weld heat treatment on duplex stainless steel weld overlay - Sim, Bernard Maxmillan (2019)
Duplex stainless steels (DSSs) are widely used in the marine environment, petro-chemical refineries, oil and gas industries because of their high corrosion resistance properties and balanced ratio of austenite and delta-ferrite phases. The objectives of this research are to analyze and evaluate the behavior of pitting corrosion, micro-hardness, microstructure and chemical dilution effects of duplex stainless steel E2209 weld overlay with the hydrogen relief (350°C), stress relief (650°C) and solid solution annealing (1050°C) heat treatments. Shield Metal Arc Welding (SMAW) process with medium heat input produced a reasonable partitioning ratio. The dilution has slightly increased in hydrogen heat treatment and a small reduction for Stress relief heat treatment. Solution annealing with water quenching at above critical point of A3 cooling temperature has shown the disappearance of heat affected zone for low alloy steel substrate. Micro-hardness has indicated a substantial fluctuation of hardness values in fusion zone. The solution annealing has shown a consistent low hardness values at the weld overlay and hardened base metal region with the present of a large amount of maternsite and noticed of equaxied ferrite structures. Ferrite count determination in region of weld metal overlay are increased at hydrogen relief temperatures and decreased at stress relief temperatures due to slow cooling which is more favorable to austenite formation. The amount of ferrite in the weld metals has significantly reduced with the solid solution anneal temperature due to sufficient time for the formation of austenite and giving optimum equilibrium fraction in the welds. The major of alloying elements which can contribute to intermetallic phases are analyzed. C, Cr and Ni chemical elements have shown fluctuation values during PWHT. Whereas, N2 has produced consistent values to prevent critical implication to nitride precipitation. The corrosion weight loss has gradually increased with the increment of PWHT temperatures. At solid solution annealing temperature, the weld metals are being restored with no significant of weight loss.